In the days of our grandmothers: a reader in Aboriginal women's history in Canada - Kelm, Mary-Ellen; Townsend, Lorna (University of Toronto Press, 2006)
From Ellen Gabriel to Tantoo Cardinal, many of the faces of Aboriginal people in the media today are women. In the Days of Our Grandmothers is a collection of essays detailing how Aboriginal women have found their voice in Canadian society over the past three centuries. Collected in one volume for the first time, these essays critically situate Aboriginal women in the fur trade, missions, labour and the economy, the law, sexuality, and the politics of representation. (Midwest).
Section: xi, 434 pages : illustrations, cartes ; 24 cm
Keywords: 1700-1799; 1800-1899; 1900-1999; 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; canada; commerce; commerce de peaux; cours; discipline; droit; droits des femmes*; droits des femmes* autochtones; famille; féminisme autochtone; histoire; histoire et politique; pol4105; premier cycle; périodes historiques; régions géographiques; science politique et droit; sciences humaines; sexualité; thématiques; travail

Idylle Saphique - Pougy, Liane de (Alteredit, 2006)
Au printemps 1899, Liane de Pougy, amie de l'écrivain jean Lorrain et ennemie jurée de Caroline Otero, rencontre une américaine de vingt-trois ans, Natalie Clifford Barney. C'est aussitôt le coup de foudre. Pendant l'été qui suit, les deux femmes vont vivre une véritable passion. C'est cette passion que Liane écrit au fur et à mesure qu'elle la vit. Idylle Saphique, paru en 1901, est un brillant témoignage de cette époque " fin de siècle ", tellement décadente et tellement tumultueuse, où le plaisir et son assouvissement règnent en maître à Paris.
Première édition: 1901
Keywords: 1800-1899; 1890-1899; 1900-1999; corps; europe; france; histoire et politique; personnes lesbiennes; périodes historiques; relations amoureuses; régions géographiques; sexualité; thématiques